PENGEMBANGAN E-MODUL UNTUK MENINGKATKAN SPATIAL VISUALIZATION INTELLIGENCE PADA MATERI PROYEKSI ORTOGONAL DI SMK NEGERI 1 SIDOARJO - Chotmi Syayidah Maulidya; Hendra Wahyu Cahyaka (Jurnal Kajian Pendidikan Teknik Bangunan, 2023)
Many students who lacked spatial visualization intelligence or spatial-visual skills found it difficult to analyze, comprehend, and interpret engineering drawings, especially when competing with DPIB skills. However, this ability can be enhanced through precise educational approaches, such as using media that aligns with the subject's concept, like e-modules. The objective of this study was to gain insights into two things: (1) the effectiveness of e-modules in enhacing spatial visualization intelligence, as assessed through student assesment in orthogonal projection material, and (2) student feedback on the e-module for learning orthogonal projection material.The study employed the RnD ASSURE research method, encompassing six steps: analyze learners; state objectives; select methods, media, and materials; utilize media and materials; require learner's participation; and evaluate and revise. The product trial phase involved a quasi-experimental pretest-posttest control group design conducted on X-DPIB students at SMK Negeri 1 Sidoarjo. The experimental group, utilizing the e-module, achieved an average n-gain value of 0.62, categorized as "Medium" effectiveness. In contrast, the control group, employing PowerPoint as the medium, obtained an average n-gain of 0.56, also falling under the "Medium" effectiveness criterion. The experimental group showed an average n-gain value of 0.62, providing empirical evidence that the e-module is more effective in enhancing student's spatial visualization intelligence than the PowerPoint used by the control group. The research data indicates that the average student feedback on the orthogonal projection e-module was favorable with an average response value of 4.59, which corresponds to a percentage of 91.7%. This percentage falls within the "Very good" qualification level.